Inside my heart : choosing to live with passion and purpose - McGraw, Robin (Nashville : Nelson Books, 2006)
Dr. Phil's wife speaks directly to the heart of every woman and challenges her to recognize and develop her unique role to lead her to satisfaction with herself, her profession, her family and anything she strives after.--From publisher description.
From my heart to yours -- A woman's heart (and mind) -- A daughter's heart : choosing my own legacy -- A heart of clarity and conviction : choosing to go after what I want -- A discerning heart : what I learned from my mother's legacy of love -- A wife's heart : choosing to do whatever makes my husband happy -- A confident heart : when I'm right, I'm right -- The heart of my home.
Keywords: Christian women -- Religious life